2004
DOI: 10.1111/j.1365-2826.2004.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of the Hypothalamic‐Pituitary‐Adrenal Axis During Maternal Deprivation

Abstract: A close contact between the dam and the litter is essential for the normal development of the hypothalamic-pituitary-adrenal (HPA) axis in rats and mice. Maternal signals, as licking and feeding, have been shown to sustain the HPA axis of the pups in a hypo-responsive state. Disruption of this mother-pup interaction by 24 h of maternal deprivation activates the otherwise quiescent stress system of the neonates, resulting in an enhanced adrenal sensitivity to adrenocorticotropic hormone (ACTH) and a decreased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 50 publications
5
84
0
1
Order By: Relevance
“…In contrast, we observed no effects of 8 h maternal separation on AVP expression in the PVN or GR expression in the CA1 region of the hippocampus. These data are in line with our previous findings, indicating that both transcripts change only in response to longer separation periods (Schmidt et al 2004). Taken together, it seems likely that the NPY-mediated activation of the HPA axis in the neonate mainly acts on CRH expressing neurons in the PVN.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, we observed no effects of 8 h maternal separation on AVP expression in the PVN or GR expression in the CA1 region of the hippocampus. These data are in line with our previous findings, indicating that both transcripts change only in response to longer separation periods (Schmidt et al 2004). Taken together, it seems likely that the NPY-mediated activation of the HPA axis in the neonate mainly acts on CRH expressing neurons in the PVN.…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that 8 h of separation are sufficient for a dramatic increase in plasma corticosterone as well as associated gene expression changes in the brain (Schmidt et al 2004). Further, these changes were accompanied (or even preceded) by alterations in peripheral metabolic signals as glucose or ghrelin.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the effects of maternal separation on physiological changes, particularly with regard to HPA axis function. Results from these studies have shown that extended periods of separation (eg 24 h) were necessary to produce robust and enduring changes in HPA function (Schmidt et al, 2004;Levine, 2002;Rots et al, 1996). In contrast, McCormick et al (1998) reported that rats that were isolated from mother and siblings for only 1 h/day from postnatal day 2 through 9 showed increased plasma corticosterone levels, much higher than normal corticosterone levels in control animals.…”
Section: Effect Of Stressmentioning
confidence: 89%
“…It may, however, seem paradoxical that the CRH mRNA levels are suppressed rather than enhanced in these structures. However, it has been established that there is a robust modulation of key HPA axis molecules at different time points as the 24-h maternal deprivation progresses (Schmidt et al, 2004). The activation of the key elements of the HPA axis, namely CRH mRNA in PVN, plasma ACTH and corticosterone, occurs between 4 and 8 h of maternal absence.…”
Section: Discussionmentioning
confidence: 99%